Introductory MEMS Fabrication and Applications - Adams, Thomas M.; Layton, Richard A.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Introductory MEMS: Fabrication and Applications is a practical introduction to MEMS for advanced undergraduate and graduate students. Part I introduces the student to the most commonly used MEMS fabrication techniques as well as the MEMS devices produced using these techniques. Part II focuses on MEMS transducers: principles of operation, modeling from first principles, and a detailed look at commercialized MEMS devices, in addition to microfluidics. Multiple field-tested laboratory exercises are included, designed to facilitate student learning about the fundamentals of microfabrication processes. References, suggested reading, review questions, and homework problems are provided at the close of each chapter. Introductory MEMS: Fabrication and Applications is an excellent introduction to the subject, with a tested pedagogical structure and an accessible writing style suitable for students at an advanced undergraduate level across academic disciplines.
Fabrication -- The substrate and adding material to it -- Creating and transferring patterns$1 (BPhotolithography -- Creating structures$1 (BMicromachining -- Solid mechanics -- Applications -- Thinking about modeling -- MEMS transducers$1 (BAn overview of how they work -- Piezoresistive transducers -- Capacitive transducers -- Piezoelectric transducers -- Thermal transducers -- to microfluidics -- Laboratories -- Microfabrication laboratories.s
Keywords: Engineering; Mechanics; Materials; Electronics; Systems engineering; Surfaces (Physics).; Engineering; Electronics and Microelectronics, Instrumentation; Circuits and Systems; Mechanics; Surfaces and Interfaces, Thin Films; Continuum Mechanics and Mechanics of Materials